The effectiveness of the CTL learning model using REACT strategy with the mind map and the influence of learning independence on students' mathematical connection ability - Nurhayati, Khomsatun Dwi; Sukestiyarno, Yohanes Leonardus; Mulyono, Mulyono (Unnes Journal of Mathematics Education, 2021)
This study aims to determine the effectiveness of the CTL learning model using REACT Strategy with the mind map and the influence of learning independence on students' mathematical connection abilities. The research was conducted at Tran Nhan Tong Senior High School, Ho Chi Minh City, Vietnam. The research sample were students of class XA1 as the experimental class that applied the CTL learning model using REACT strategy with mind map and class XA2 as the control class that applied the expository learning model selected based on cluster random sampling. The research data were obtained through tests, questionnaires, and observations. The results showed that 1) the mathematical connection ability of the students that use CTL with the mind map-assisted REACT strategy reached the completeness criteria, 2) the mathematical connection ability of students that use CTL with mind map-assisted REACT strategy higher than the mathematical connection ability of students that use expository learning, and 3) there is a positive effect of student learning independence on the mathematical connection ability of students that use CTL with mind map-assisted REACT strategy.